2015
DOI: 10.1159/000369815
|View full text |Cite
|
Sign up to set email alerts
|

Differential Membrane Expression of Toll-Like Receptors and Intracellular Cytokine Induction in Peripheral Blood Monocytes of Patients with Chronic Kidney Disease and Diabetic Nephropathy

Abstract: Background: Toll-like receptors (TLRs) are key players in the innate immune system whose activation leads to an inflammatory response. Inflammation plays an important role in the pathogenesis of chronic kidney disease (CKD) and diabetes mellitus. The aim of our study was to assess the proinflammatory state of nondialysis CKD patients by evaluating the membrane expression of TLR2 and TLR4 and the intracellular IL-1β and IL-6 production in response to the ligand Pam3Cys-Ser-(Lys)4 (Pam3CSK4). Methods: 85 nondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…45,46 Zikou et al provided evidence that the effect of CKD on monocyte cytokine production may depend on CKD etiology with monocyte responses increased in diabetic kidney disease and attenuated in other CKD etiologies. 47 Variations in the isolation procedure, experimental technique, and severity of CKD studied may partially explain these discrepant results. Our data suggest that monocyte capacity to produce TNF and IL-1 β , including the rapid and intense response of HLA-DR hi IMs, is preserved—neither increased nor suppressed—in stable non–dialysis-dependent CKD.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Zikou et al provided evidence that the effect of CKD on monocyte cytokine production may depend on CKD etiology with monocyte responses increased in diabetic kidney disease and attenuated in other CKD etiologies. 47 Variations in the isolation procedure, experimental technique, and severity of CKD studied may partially explain these discrepant results. Our data suggest that monocyte capacity to produce TNF and IL-1 β , including the rapid and intense response of HLA-DR hi IMs, is preserved—neither increased nor suppressed—in stable non–dialysis-dependent CKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been hypothesized that TLR4 may be introduced as an important PRR involved in the induction of inflammation in the elderly population, because the antagonists of TLR4 can inhibit the interaction of ligands with TLR4 and block its intracellular signaling and decreased inflammation during aging 11 . Additionally, it has been proven that several aging complications like type 2 diabetes, cardiovascular diseases and kidney diseases have a potential link with TLR4 and its intracellular signaling molecules, which play an important role in the pathogenesis of the human diseases [12][13][14][15][16] . Thus, it seems that TLR4 can play key roles during aging inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…TLR2 and/or TLR4 are actively involved in the development of kidney diseases, such as ischemia-reperfusion injury, cisplatin-induced nephrotoxicity and crescentic glomerulonephritis (1113). TLR2 and/or TLR4 are also required for the development of DN (1418). In streptozotocin (STZ)-induced diabetic animal models, TLR2 and TLR4 expression is enhanced, accompanied by the activation of their downstream signaling pathways (1416).…”
Section: Introductionmentioning
confidence: 99%
“…In streptozotocin (STZ)-induced diabetic animal models, TLR2 and TLR4 expression is enhanced, accompanied by the activation of their downstream signaling pathways (1416). Clinical studies have indicated that TLR2 and TLR4 expression and activity are significantly upregulated in diabetic patients (17,18), indicating that TLR2 and/or TLR4 may represent targets for the prevention of DN. Previous reports showed that TLR2 primarily signals through the MyD88-dependent pathway to induce inflammation (14).…”
Section: Introductionmentioning
confidence: 99%